Investigating stable isotope effects and moisture trajectories for rainfall events in Johannesburg, South Africa - Khahliso Leketa; Tamiru Abiye (Water SA, 2020)
This study investigated the isotopic composition of daily rainfall in Johannesburg from November 2016 to October 2018. The moisture sources and trajectories for rainfall events of extreme isotopic signatures were deduced using the Hybrid Single Particle Lagrangian Integrated Trajectory model (HYSPLIT). The results from time series and regression analysis show temperature and amount effects, with low coefficient of determination (R2) values of 0.21 and 0.12, respectively. The rainfall with amounts of